Voltaire’s Breadfruit - Russell Fielding (Plant Perspectives)
The British Government-facilitated introduction of breadfruit trees (Artocarpus altilis) from the Pacific to the Caribbean during the late eighteenth century was a notable feat of economic botany, but the identities of the earliest originators of the idea remain unclear. Previous historical scholarship has focused mainly upon the role of Joseph Banks as the prime mover behind the scheme, while more investigative scholarship has identified one of Banks’s correspondents, Valentine Morris, as having made an early suggestion of the idea in writing. This focus on Banks and Morris, however, may have overlooked or understudied even earlier origins of the idea. After discussing several key individuals involved in the inception of the breadfruit project, this article then considers a series of passages on breadfruit in the writings of Voltaire and presents a hypothetical pathway by which those involved in the actual transfer of breadfruit from the Pacific to the Caribbean, including Banks via Morris, may have been influenced by the French philosopher.